Household economics, information sources and annuity choices: Annuitisation preferences of members of the Slovak private pension pillar - Vladimír Baláž (Economies, 2023)
This research uses representative survey data to elicit the annuitisation preferences of members of the Slovak-funded private pension pillar. The research explores the impact of socioeconomic and sociodemographic variables, as well as some exogenous factors on annuity choices. The following choices are analysed: (i) taking an annuity upon retirement; (ii) delaying the uptake of an annuity and accumulating savings beyond the official age of retirement; and (iii) leaving accumulated wealth to heirs (bequest motive). The paper provides some original contributions. Firstly, it relates annuity choices to intrafamily risk sharing. Attention is paid to household structure, income levels, and the presence of dependent children. Secondly, the importance of diverse information resources on the formation of annuity preferences is examined. We found that professional advice provided by financial institutions and government bodies was associated with higher probabilities of annuity uptake. A disproportional reliance on informal channels may explain the higher preference towards bequest motives in rural areas. Thirdly, annuity choices are studied in relation to alternative sources of income in old age. A combination of social security pensions and bequest-sharing arrangements may offset the need for the annuitisation of pension wealth.
Keywords: 330; annuities; intrafamily risk sharing; bequest motives; accumulation motives